Molecular buffer, storage and delivery using a PANDA ring resonator and an optical router - Jalil, Muhammad A.; Roslan, Muhammad S.; Mohamad, Azam; Suwanpayak, Nathaporn; Raman, K.; Teeka, Chat; Ali, Jalil; Yupapin, Preecha P. (My University, 2011)
A novel design of molecular buffer for molecule storage and delivery using a PANDA ring resonator is proposed. The optical vortices can be generated and controlled to form the trapping tools in the same way as the optical tweezers. In theory, the trapping force is formed by the combination between the gradient field and scattering photons, which is reviewed. By using the intense optical vortices generated within the PANDA ring resonator, the required molecules can be trapped and moved (transported) dynamically within the wavelength router or network, in which the molecular buffer can be performed within the wavelength router before reaching the required destination. The advantage of the proposed system is that a transmitter and receiver can be formed within the same system, which is available for molecule storage and transportation. Relevant patents are also reviewed in this manuscript. © 2011 Bentham Science Publishers Ltd.
Keywords: Molecular buffer; Molecular memory; Molecular repeater; Molecular transceiver